La evaluación del vocabulario en la educación preescolar: el TEVOPREESC - Murillo Rojas, Marielos (2012)
This article deals with the language evaluation of preschoolers. It focuses on TEVOPREESC, which is a Costa Rican Test for preschool students between 3-6 years old. This instrument was elaborated by the Instituto de Investigaciones Linguísticas of the Universtiy of Costa Rica.